Long-Term Follow-Up of Combination of B-Cell Maturation Antigen and CD19 Chimeric Antigen Receptor T Cells in Multiple Myeloma. Issue 20 (10th July 2022) - Wang, Ying; Cao, Jiang; Gu, Weiying; Shi, Ming; Lan, Jianping; Yan, Zhiling; Jin, Lai; Xia, Jieyun; Ma, Sha; Liu, Yang; Li, Hujun; Pan, Bin; et al.
Abstract : PURPOSE: A combination of anti–B-cell maturation antigen (BCMA) and anti-CD19 chimeric antigen receptor (CAR) T cells induced high response rates in patients with relapsed or refractory (R/R) multiple myeloma (MM), but long-term outcomes have not been assessed yet. PATIENTS AND METHODS: In this single-arm, phase II trial, patients with R/R MM received a combination of anti-BCMA CAR T cells and anti-CD19 CAR T cells at a dose of 1 × 10 6 cells/kg, after receiving a conditioning chemotherapy consisting of cyclophosphamide and fludarabine. The overall response, long-term outcomes, and safety were assessed, as were their associations with clinical and disease characteristics. RESULTS: Of 69 enrolled patients, 62 received the combined infusion of anti-BCMA and anti-CD19 CAR T cells with a median follow-up of 21.3 months. The overall response rate was 92% (57/62), and complete response or better was observed in 37 patients (60%). Minimal residual disease–negativity was confirmed in 77% (43/56) of the patients with available minimal residual disease detection. The estimated median duration of response was 20.3 months (95% CI, 9.1 to 31.5). The median progression-free survival was 18.3 months (95% CI, 9.9 to 26.7), and the median overall survival was not reached. Patients with extramedullary disease had significantly inferior survival. Fifty-nine patients (95%) had cytokine release syndrome, with 10% grade 3 or higher. Neurotoxic events occurred in seven patients (11%), including 3% grade 3 or higher. Late adverse effects were rare, except for B-cell aplasia, hypogammaglobulinemia, and infections. CONCLUSION: The combination of anti-BCMA and anti-CD19 CAR T cells induced durable response in patients with R/R MM, with a median progression-free survival of 18.3 months and a manageable long-term safety profile. Abstract :